PENGARUH DIMENSI CUSTOMER EXPERIENCE TERHADAP REVISIT INTENTION DI BALI ZOO PADA MASA NEW NORMAL - Friseyla, Natasya; Dewi, LGLK.; Sudiarta, I Nyoman (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023), 2023)
This study aims to determine the effect of customer experience dimensions in terms of sense, feel, think, act, and relate to revisit intention at Bali Zoo during the new normal period. Determination of the sample used is through purposive sampling method with the criteria of domestic tourists who have visited the Bali Zoo during the new normal. The data collection used is the distribution of online questionnaires through social media to domestic tourists of Bali Zoo as many as 100 respondents, observation, documentation, and literature study. The data analysis technique used is descriptive quantitative using measurement model evaluation, structural model evaluation, and hypothesis testing using SmartPLS software version 3.3.9. The results of this study indicate that sense, think, and relate have a positive and significant effect on revisit intention; feel has a negative and significant effect on revisit intention; and act has a positive and insignificant effect on revisit intention at Bali Zoo during the new normal period. The influence generated from customer experience in terms of sense, feel, think, act, and relate to revisit intention is 52% which is moderate. The resulting predictive relevance value is 0.378.